2014
DOI: 10.1371/journal.pone.0110110
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Evaluation of PMTCT Uptake in Nyanza Province, Kenya

Abstract: IntroductionFacility-based assessments of prevention of mother-to-child HIV transmission (PMTCT) programs may overestimate population coverage. There are few community-based studies that evaluate PMTCT coverage and uptake.MethodsDuring 2011, a cross-sectional community survey among women who gave birth in the prior year was performed using the KEMRI-CDC Health and Demographic Surveillance System in Western Kenya. A random sample (n = 405) and a sample of women known to be HIV-positive through previous home-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 27 publications
4
27
1
Order By: Relevance
“…The low rates of HIV testing in women attending late for ANC in our study have also been found in Vietnam [16], and again in Zimbabwe where women with fewer ANC visits declined HIV testing due to fear of disclosure and the need to have partners' consent [17]. The high uptake of Option B+ in our study was similar to what was found in a recent study in Kenya [14]. While most of the reasons for declining Option B+ were unspecified and are therefore speculative, in Malawi, the fear of HIV disclosure was the reason most commonly given for refusal to take up ART [18].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The low rates of HIV testing in women attending late for ANC in our study have also been found in Vietnam [16], and again in Zimbabwe where women with fewer ANC visits declined HIV testing due to fear of disclosure and the need to have partners' consent [17]. The high uptake of Option B+ in our study was similar to what was found in a recent study in Kenya [14]. While most of the reasons for declining Option B+ were unspecified and are therefore speculative, in Malawi, the fear of HIV disclosure was the reason most commonly given for refusal to take up ART [18].…”
Section: Discussionsupporting
confidence: 89%
“…We also encountered missing data due to incomplete documentation in registers and our findings from just two districts further limit our ability to infer study findings to the general population. Despite these limitations, the general high level of HIV testing uptake in this study is encouraging and comparable to findings from a community-based study in Kenya [14]. HIV testing uptake was also slightly better when compared to previous demographic and health survey (DHS) data from sub-Saharan Africa which found an HIV testing uptake of 73% in ANC clinics in Zimbabwe [15].…”
Section: Discussionsupporting
confidence: 78%
“…The methodology of the parent study has previously been described [ 20 ]. A list of women in the KEMRI-CDC HDSS area who had delivered in 2010 was generated.…”
Section: Methodsmentioning
confidence: 99%
“…Two-hundred children aged 6 weeks to 17 months (inclusive) at first vaccination were enrolled at two study sites in Western Kenya, KEMRI/WRAIR, Kisumu and KEMRI/CDC, Siaya. The sites are located in an area with high malaria prevalence (38 % in children 0-14 years) 14 and vertical transmission rates of HIV (between 7 -15% in the context of increased uptake of PMCT) 15,16 . Infants and children known to be HIV infected (documented positive DNA PCR) were included, whether or not they were on antiretroviral medication.…”
Section: Study Site and Participantsmentioning
confidence: 99%